Shooting ball accuracy with U16 soccer players after preparation period - Gardasevic, J.; Bjelica, D. (SportMont, 2019)
The main aim of the research was to identify a level of quantitative changes of the shooting ball accuracy with U16 soccer players under the influence of the programmed soccer training of six weeks a summer preparation period. The training programme covered 44 training units. The research was made on a sample of 120 soccer players. For the assessment of shooting ball accuracy the three tests were used: Straight foot accuracy in the vertical target, Elevation foot accuracy in the vertical target and Elevation head accuracy in the vertical target. In the area of comparative statistics, used t-test for big paired samples. Based on the numerical values of the t-test it can be concluded that there are statistically significant differences in all three variables to estimate the shooting ball accuracy. In this research the authors were guided by the fact that this kind of training program in preparation period, where dominates the situational model training is very effective in terms of raising the shooting ball accuracy with U16 soccer players, because the model that is used in this training period abounds in exercises in which dominates the shooting ball accuracy, in straight and elevation line. The obtained results can be directed towards innovation plans and programs in the preparation period, and the adaptation of the same needs of the respective population.